2017
DOI: 10.1242/bio.025809
|View full text |Cite
|
Sign up to set email alerts
|

Senescence gives insights into the morphogenetic evolution of anamniotes

Abstract: Senescence represents a mechanism to avoid undesired cell proliferation that plays a role in tumor suppression, wound healing and embryonic development. In order to gain insight on the evolution of senescence, we looked at its presence in developing axolotls (urodele amphibians) and in zebrafish (teleost fish), which are both anamniotes. Our data indicate that cellular senescence is present in various developing structures in axolotls (pronephros, olfactory epithelium of nerve fascicles, lateral organs, gums) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 18 publications
5
19
1
Order By: Relevance
“…More recently, it has also been shown to be a reliable method, with which the programmed cellular senescence was identified that occurs during embryonic development. [9][10][11][12][13][14][15][16] However, the present results demonstrate that the expression of cytochemically detectable β-galactosidase pH 6.0 activity is not limited to senescent cells since it was detected in subpopulations of differentiated retinal cells and in RPE cells. Indeed, in the literature, one finds that several authors have questioned whether SA-β-GAL is actually a reliable marker of cellular senescence in vivo and in vitro.…”
Section: Sa-β-gal Activity In the Rpecontrasting
confidence: 55%
See 3 more Smart Citations
“…More recently, it has also been shown to be a reliable method, with which the programmed cellular senescence was identified that occurs during embryonic development. [9][10][11][12][13][14][15][16] However, the present results demonstrate that the expression of cytochemically detectable β-galactosidase pH 6.0 activity is not limited to senescent cells since it was detected in subpopulations of differentiated retinal cells and in RPE cells. Indeed, in the literature, one finds that several authors have questioned whether SA-β-GAL is actually a reliable marker of cellular senescence in vivo and in vitro.…”
Section: Sa-β-gal Activity In the Rpecontrasting
confidence: 55%
“…Its expression is detected in various embryonic tissues in narrow time windows in all the vertebrates analyzed so far from fish to mammals. [9][10][11][12][13][14][15][16] In all these studies, SA-β-GAL expression is usually linked with degenerating structures, and programmed cell senescence has been described as being accompanied by programmed cell death. Programmed cell death also plays a crucial role in the development of the vertebrate visual system.…”
Section: Sa-β-gal Activity and Apoptotic Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific SAβG staining was detected in the otic vesicle, neural roof plate, limb buds, and the mesonephros, among other locations. Although these phenotypes have been characterized in detail in mouse embryos, developmental senescence has also been identified in human, chick, quail, axolotl, xenopus and zebra fish embryos (Nacher et al, 2006;Muñoz-Espín et al, 2013;Storer et al, 2013;Lorda-Diez et al, 2015;Davaapil et al, 2017;Villiard et al, 2017), indicating that it represents an evolutionary conserved mechanism. Interestingly, physiological senescence has also been observed in the placenta, where it has been associated to trophoblast cell fusion (Chuprin et al, 2013), as well as in embryonically-derived membranes, where its dysregulation could be related to pregnancy and parturition defects (Cha and Aronoff, 2017).…”
Section: Developmental Senescencementioning
confidence: 99%